A new displacement bound technique for rigid plastic continua subjectet to strong dynamic loading at large deflections II. - The, Vu Van; Tinh, Tran Ba (Vietnam Journal of Mechanics, 1987)
The method developed in [ 1] is applied herein in order to obtain lower hound to large displacements of the hinge supported circular plate acted on by impulsively, uniformly distributed loading. The plate is made from rigid and perfectly plastic material which yields according to the yield condition shown in fig- 1· The lower bound (1.21) is obtained when the dynamically admissible displacement and velocity are chosen in separated variable form which is a scalar time function multiplied by a vector shape function of space variable (1.13). In the case when W, Ẇ * are chosen in form (1.22). [comparison of the obtained estimate Eq (1.24) with previous solution of the same problem [1], upper bound [2] and experimental date [3] are presented in fig. 2